Mobile phone addiction in Tibetan and Han Chinese adolescents. Issue 3 (4th December 2018) - Lu, Li; Xu, Dan‐Dan; Liu, Huan‐Zhong; Zhang, Ling; Ng, Chee H.; Ungvari, Gabor S.; Wu, Weng Tong; Xiang, Yi‐Fan; An, Feng‐Rong; Xiang, Yu‐Tao
Abstract: Purpose: To compare mobile phone addiction (MPA) patterns between Tibetan and Han adolescents in China. Design and Methods: The study was carried out in two provinces of China. The Mobile Phone Addiction Scale (MPAS) was used to assess MPA. Findings: Seven hundred and five Tibetan and 606 Han students participated in the study. The MPAS total score was 24.4 ± 11.4 in the whole sample; 27.3 ± 10.8 and 20.9 ± 11.2 in Tibetan and Han students, respectively. Quality of life (QOL) in the physical, psychological, social, and environmental domains was negatively associated with MPA. Practice Implications: Compared with Han students, Tibetan students were found to have more severe MPA. Given its negative impact on QOL, appropriate measures for the prevention of MPA should be developed, particularly for Tibetan middle school students.